Comparison of E-Book Acquisitions Strategies Across Disciplines Finds Differences in Cost and Usage - Costello, Laura (Evidence Based Library and Information Practice, 2017)
A Review of: Carrico, S.B., Cataldo, T.T., Botero, C., & Shelton, T. (2015). What cost and usage data reveals about e-book acquisitions: Ramifications for collection development. ALCTS, 59(3). Retrieved from https://journals.ala.org/lrts/article/view/5752/7199 Abstract Objective – To compare e-book cost-usage data across different acquisitions styles and disciplines. Design – Case study. Setting – A public research university serving an annual enrollment of over 49,000 students and employing more than 3,000 faculty members in the Southern United States. Subjects – Cost and usage data from 15,006 e-books acquired by the Library through packages, firm orders, and demand-driven acquisitions. Methods – Data was collected from publishers and vendors across the three acquisitions strategies. Usage, cost, and call number information was collected for the materials purchased via firm order or demand driven acquisitions and these were sorted into disciplines based on the call number assigned. Discipline, cost, and use were determined for each package collection as a whole because information on individual titles was not provided by the publishers. The authors then compared usage and cost across disciplines and acquisitions strategies. Main Results – Overall, e-books purchased in packages had a 50% use rate and an average cost per use of $3.39, e-books purchased through firm orders had a 52% use rate and an average cost per use of $22.21, and e-books purchased through demand driven acquisitions had an average cost per use of $8.88 and 13.9 average uses per title. Package purchasing was cost effective for science, technology, engineering, and mathematics (STEM) materials and medicine (MED) materials. Demand driven acquisition was a particularly good strategy for humanities and social sciences (HSS) titles. Conclusion – There are differences between the acquisitions strategies and disciplines in cost and use. Firm orders had a higher cost per use than the other acquisitions strategies.